Let f = -10 + 16. Solve -3*g - f = -5*g for g.
3
Suppose -h - m - 5 = -14, -4*h + 40 = 5*m. Solve o + 3 = h for o.
2
Let n = -19 + 23. Solve n*f + 16 = -0 for f.
-4
Let v(n) = -n + 4. Let c be v(7). Let g be -1*12/c - 2. Solve -g*o + 25 = -7*o for o.
-5
Let w = 17 - 8. Let q = -5 + w. Solve h = -q*h - 15 for h.
-3
Suppose t - 3*t = 0. Suppose -v + 11 - 2 = t. Let s be 146/v + (-2)/9. Solve 0*r + 4*r - s = 0 for r.
4
Let u be (6⁄5)/((-2)/(-5)). Suppose -u*w + 2 + 7 = 0. Suppose 3*h = -5*a + 4, -a + h - 4*h = 4. Solve a*l = -w*l for l.
0
Let a = 16 - 8. Suppose r = -r + a. Solve 0 = -r*x - 8 - 0 for x.
-2
Let q = -12 - -18. Solve q*t + 20 = 2*t for t.
-5
Suppose 5*b - 5*t - 10 = 0, -b - 4 = -5*t + t. Suppose -b*j = -j - 33. Suppose -2 = -g + j. Solve -4 = -3*x - g for x.
-3